Pelaksanaan Fungsi Badan Penanggulangan Narkotika di Kabupaten Sidrap - Suharman Suharman; Parakkasi Tjaija; Muhammad Idris (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
The aim of this research was to find out the function of Narcotic Tackling Agency in Sidrap. The research method is descriptive-quantitative. The research type are survey with sampling using random sampling techniques as many as 30 people including 20 people and 10 policemen and the employees of BPNK office. The data was collected through observation, interviews, questionnaires and quantitative analysis. Based on the research result obtained on the implementation of Narcotic Tackling Agency in Sidrap has been performing its duties and functions in the prevention of the abuse of illicit traffic of narcotics that includes overcoming the problem of narcotics, preparation of technical policy, prevention and eradication of the use of illicit trafficking, law enforcement, treatment and rehabilitation, education and time on narcotics, prevention strategies and outreach, law enforcement strategies and strategies Therapy and Rehabilitation. The factors that affect were the implementation Narcotic Tackling Agencyin Sidrap include the cost of implementation, lack of awareness factor coordination and cooperation, education factors and special training (Training), and social factors on the prosecution. Keywords: the tackling of narcotic Tujuan dari penelitian ini adalah untuk mengetahui fungsi Badan Penanggulangan Narkotika di Kabupaten Sidrap. Jenis penelitian ini adalah deskriptif-kuantitatif. Tipe penelitian ini adala penelitian survey dengan penarikan sampel menggunakan tehnik random sampling sebanyak 30 orang diantaranya 20 orang masyarakat dan 10 orang polisi dan pegawai Kantor BPNK. Data di kumpulkan dengan observasi, wawancara, kuesioner, dan di analisis secara kuantitatif. Berdasarkan hasil penelitian maka diperoleh mengenai Pelaksanaan tugas badan penanggulangan narkotika di Kabupaten Sidrap telah menjalankan tugas dan fungsinya dalam pencegahan penyalahgunaan peredaran gelap Narkotika yang meliputi penanggulangan masalah narkotika, penyusunan kebijakan teknis, pencegahan dan pemberantasan penggunaan peredaran gelap narkotika, penegakan hokum, terapi dan rehabilitasi, pendidikan dan waktu mengenai narkotika, strategi pencegahan dan penyuluhan, strategi Penegakan hukum, dan strategi Terapi dan Rehabilitasi. Faktor-faktor yang mempengaruhi pelaksanaan tugas badan penanggulangan narkotika di Kabupaten Sidrap meliputi faktor biaya pelaksanaan, faktor kurangnya kesadaran berkoordinasi dan bekerjasama, faktor pendidikan dan latihan khusus (Diklat), dan faktor penindakan dalam sosial. Kata kunci: penanggulangan, narkotika